Randomized Phase II Trial of Exercise, Metformin, or Both on Metabolic Biomarkers in Colorectal and Breast Cancer Survivors. Issue 1 (20th November 2019) - Meyerhardt, Jeffrey A; Irwin, Melinda L; Jones, Lee W; Zhang, Sui; Campbell, Nancy; Brown, Justin C; Pollak, Michael; Sorrentino, Alexandra; Cartmel, Brenda; Harrigan, Maura; Tolaney, Sara M; Winer, Eric; et al.
Abstract: Background: Observational data support inverse relationships between exercise or metformin use and disease outcomes in colorectal and breast cancer survivors, although the mechanisms underlying these associations are not well understood. Methods: In a phase II trial, stage I–III colorectal and breast cancer survivors who completed standard therapy were randomly assigned to structured exercise or metformin or both or neither for 12 weeks. The primary outcome was change in fasting insulin levels; secondary outcomes included changes in other blood-based energetic biomarkers and anthropometric measurements. Analyses used linear mixed models. Results: In total, 139 patients were randomly assigned; 91 (65%) completed follow-up assessments. Fasting insulin levels statistically significantly decreased in all three intervention arms (−2.47 μU/mL combination arm, −0.08 μU/mL exercise only, −1.16 μU/mL metformin only, + 2.79 μU/mL control arm). Compared with the control arm, all groups experienced statistically significant weight loss between baseline and 12 weeks (−1.8% combination arm, −0.22% exercise only, −1.0% metformin only, +1.55% control). The combination arm also experienced statistically significant improvements in the homeostatic model assessment for insulin resistance (−30.6% combination arm, +61.2% control) and leptin (−42.2% combination arm, −0.8% control), compared with the control arm. The interventions did not change insulin-like growth factor–1 or insulin-like growth factor binding protein–3 measurements as compared with the control arm. Tolerance to metformin limited compliance (approximately 50% of the participants took at least 75% of the planned dosages in both treatment arms). Conclusions: The combination of exercise and metformin statistically significantly improved insulin and associated metabolic markers, as compared to the control arm, with potential greater effect than either exercise or metformin alone though power limited formal synergy testing. Larger efforts are warranted to determine if such a combined modality intervention can improve outcomes in colorectal and breast cancer survivors.